2010
DOI: 10.21608/eajbsc.2010.16264
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological and behavioral effects of Chlorfluazuron on pheromone production and perception of Tribolium castaneum (Coleoptera: Tenebrionidae).

Abstract: Chlorfluazuron (Atabron) is an insect growth regulator (IGR) belongs to benzoylphenyl urea for controlling the major insect pests. The present work aims to investigate the toxicological and biological effects of Chlorfluazuron on the 4th larval instar of rust red flour beetle, Tribolium castaneum at different concentrations (0.1, 0.5, 1, 5 and 10 ppm) under laboratory conditions. The results revealed high significant mortality in larvae, pupae and adults. The obtained results showed significant decrease in adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
3
1
0
Order By: Relevance
“…The other pheromone that males emit appeared to be an aggregation pheromone produced by them to gather with the population for feeding. This agreed with Abdu et al (1985), who used radiation against the rust-red flour beetle; Chen et al (1988), who used juvenile hormone analogue and fenoxycarb on Ips paraconfusus and Bakr et al (2010), who used T. castaneum. Besides, Ruther et al (2007) reported that sex pheromones produced by an untreated male attracted females in the parasitic jewel wasp, Nasonia vitripennis.…”
Section: Discussionsupporting
confidence: 88%
“…The other pheromone that males emit appeared to be an aggregation pheromone produced by them to gather with the population for feeding. This agreed with Abdu et al (1985), who used radiation against the rust-red flour beetle; Chen et al (1988), who used juvenile hormone analogue and fenoxycarb on Ips paraconfusus and Bakr et al (2010), who used T. castaneum. Besides, Ruther et al (2007) reported that sex pheromones produced by an untreated male attracted females in the parasitic jewel wasp, Nasonia vitripennis.…”
Section: Discussionsupporting
confidence: 88%
“…The present investigation reported that the larval mortality basically resulted from molting failure with incomplete life cycle and death within the cuticle. Similar results were recorded with Tribolium castaneum [27] , Spodoptera littoralis [28,29] , and Musca domestica [22,30] . In addition, LF proved to be more toxic at all concentration levels than CF inducing larval mortality, larval deformation, and reduction of pupation percent.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, small sized and shrunken larvae were clearly observed. Similar deformations were recorded on larvae of M. domestica [22,31,33] , T. castaneum [27] , L. botrana [34] , S. littoralis [34,37] , and on B. odoriphaga [38] . Furthermore, the two tested CSIs treatments led to formation of larval-pupal intermediates.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation